Preliminary Memorandum on the Fourth Five Year Plan Union Territory of Delhi - Planning Commission (Planning Commission)
The Union Territory of Delhi occupies a peculiar place in the country. It is the metropolis of India and public opinion hare is extremely sensitive and critical of shortcomings. a high degree of achievement and efficiency is expected from the Administration in all spheres of its activities. The problems concerning Delhi are both urban as wall as rural, predominantly urban in character, although the welfare and well-being of its rural inhabitants have also to be given due importance.
Union Territory of Delhi